QT Wave Dispersion in Patients With Major Depressive Disorder - Korkmaz, Sevda; Aksoy, Dilek Bakiş; Çakar, Mustafa; Özgüler, Murat; Sarioğlu, Güney; Korkmaz, Hasan (Physicians Postgraduate Press Inc., 2020)
Objective: A limited number of studies have investigated QT wave dispersion (QTd) in depressive disorder. The objective of this study was to investigate whether QTd differed in patients diagnosed with depression compared to a control group and whether the difference correlated with the depression and anxiety scores. Methods: Forty patients diagnosed with major depressive disorder (DSM-5 criteria) who did not receive their first treatment after the first episode were included in the study. Forty healthy individuals with similar sociodemographic characteristics were included in the control group. A sociodemographic and clinical data form, the Beck Depression Inventory, and the Beck Anxiety Inventory were given to all patients. Electrocardiograms were evaluated in a single-blind setting by the same cardiologist. The longest QT interval (QTmax) and the shortest QT interval (QTmin) were calculated. Heart rate–corrected QTmax (QTcmax) and QTmin (QTcmin) were calculated using the Bazett formula (QT[ms]/?R-R). The difference between QTcmax and QTcmin was accepted as the corrected QT dispersion (QTcd). The study was conducted from December 2018–March 2019. Results: No statistically significant difference was found between patient and control groups on the basis of age, sex, body mass index, or smoking. Beck Anxiety Inventory and Beck Depression Inventory scores of the patient group (28.48 ± 12.39 and 32.2 ± 11.58, respectively) were significantly higher compared to the control group (2.7 ± 3.41 and 2.75 ± 3.2, respectively). The patient group QTcmax (419.8 ± 24.46) and QTcd (42.55 ± 17.47) values were significantly higher compared to the QTcmax (405.2 ± 24.54) and QTcd (30.48 ± 9.25) values of the control group. There was a positive correlation between QTcd, QTcmax, and anxiety and depression scores. Conclusions: QTcd values of depressed patients were higher than those of the healthy controls, and there was a positive correlation between QTcd and depression and anxiety scores. © 2020 Physicians Postgraduate Press, Inc.
Keywords: Adult; Anxiety; Arrhythmias, Cardiac; Case-Control Studies; Depressive Disorder, Major; Electrocardiography; Female; Humans; Male; Psychiatric Status Rating Scales; Severity of Illness Index; adult; anxiety; case control study; complication; electrocardiography; female; heart arrhythmia; human; major depression; male; pathophysiology; psychological rating scale; severity of illness index